The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1371/journal.pone.0078655
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Apnea and the Risk of Dementia: A Population-Based 5-Year Follow-Up Study in Taiwan

Abstract: BackgroundSleep apnea (SA) has been associated with cognitive impairment. However, no data regarding the risk of dementia in patients with SA has been reported in the general population. This retrospective matched-control cohort study was designed to estimate and compare the risk of dementia in SA and non-SA patients among persons aged 40 and above over a 5-year period follow-up.MethodsWe conducted a nationwide 5-year population-based study using data retrieved from the Longitudinal Health Insurance Database 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
91
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(102 citation statements)
references
References 29 publications
2
91
0
9
Order By: Relevance
“…Among 298 older women (mean age: 82.3 years), those with SDB, had an increased risk of developing cognitive impairment, compared to those without SDB (9). A 5-year population-based cohort study involving nearly 8,000 subjects, also demonstrated that SDB patients had 1.70-times greater risk of developing dementia compared to age-and sex-matched non-SDB patients, and its statistical significance persisted in the 50-59 [adjusted hazard ratio (HR): 3.63; 95% CI, 1.67-7.88] years old and ≥70 (adjusted HR: 1.53; 95% CI, 1.01-2.33) years old groups (10). Because of the limited data on the relationship between SDB and CV morbidity or mortality in the elderly, the applicability of the results derived from the younger or middle-aged population is uncertain.…”
Section: The Prevalence and Characteristics Of Sdb In The Elderlymentioning
confidence: 89%
“…Among 298 older women (mean age: 82.3 years), those with SDB, had an increased risk of developing cognitive impairment, compared to those without SDB (9). A 5-year population-based cohort study involving nearly 8,000 subjects, also demonstrated that SDB patients had 1.70-times greater risk of developing dementia compared to age-and sex-matched non-SDB patients, and its statistical significance persisted in the 50-59 [adjusted hazard ratio (HR): 3.63; 95% CI, 1.67-7.88] years old and ≥70 (adjusted HR: 1.53; 95% CI, 1.01-2.33) years old groups (10). Because of the limited data on the relationship between SDB and CV morbidity or mortality in the elderly, the applicability of the results derived from the younger or middle-aged population is uncertain.…”
Section: The Prevalence and Characteristics Of Sdb In The Elderlymentioning
confidence: 89%
“…Согласно существующим данным, риск развития КН, а также прогрессирования лёгких КН до деменции снижается при соблюдении пра-вильного режима питания (средиземномор-ской диеты [4-8] с высоким содержанием продуктов растительного происхождения) и создании когнитивного резерва, адекватной физической нагрузки, снижении артериаль-ного давления. Кроме того, ряд авторов ука-зывают на актуальность нарушений сна для развития КН [9][10][11][12][13].…”
unclassified
“…Chang и соавт. показали, что риск развития деменции прямо связан с предшес-твующими нарушениями сна у пациента [9,10]. В выполненном ранее исследовании M. Jelicic и соавт.…”
unclassified
“…17,18 Recently, epidemiologic studies have identifi ed a link between both OSA and insomnia, and subsequent development of dementia. 19,20 With respect to OSA, a variety of neuroimaging studies suggest evidence of brain neuronal loss or dysfunction. 21 Gray matter abnormalities also have been observed some, [22][23][24] but not all studies of patients with chronic insomnia.…”
mentioning
confidence: 99%